PRELIMINARY PHYTOCHEMICAL ANALYSIS AND ANTHELMINTIC ACTIVITY OF THE AQUEOUS EXTRACT OF OCIMUM SANCTUM (LINNAEUS, 1767) LEAVES (GREEN AND BLACK) AGAINST COTYLOPHORON COTYLOPHORUM (FISCHOEDER, 1901) - R. JOTHI KARUMARI,; K. VIJAYALAKSHMI,; S. EZHILARASI BALASUBRAMANIAN, (International Journal of Pharma and Bio Sciences, 2014)
One of the major sources of wool and meat production is sheep. But sheep are affected mostly by helminthiasis, the most important animal disease which leads to heavy production loss. Cotylophoron cotylophorum is one of the trematode parasites that cause helminthiasis in sheep. Since chemotherapeutic anthelmintics create resistance and side effects, there is a need for an alternative plant based anthelmintics, which could be effective in expelling these worms. Ocimum sanctum, which is the most sacred herb of India, is of two varieties Rama Tulsi (green) and Krishna Tulsi (black). Apart from religious significance it has got amazing number of health benefits. The present investigation deals with the comparison of phytochemical constituents and anthelmintic activity in the aqueous extract of the two leaf varieties (green and black) of O. sanctum against Cotylophoron cotylophorum. The results of the preliminary phytochemical constituents revealed that the secondary metabolites like triterpenoid, flavonoid, phenol, tannin, alkaloid, saponin and acid were present and steroid was absent in both leaf varieties (green and black) of O. sanctum. Though, dose dependent anthelmintic activity was observed in both the leaf varieties, black leaves are with more efficacy than green.